Spontaneous closure of isolated ventricular septal defect in the first year - Predojević Samardžić, Jelica; Marić, Nina; Ljuboja, Olivera (Scripta Medica, 2023)
Background/Aim: Ventricular septal defect (VSD) is the most common congenital heart anomaly that in many cases closes spontaneously. The spontaneous closure (SC) rate of VSD varies widely between studies. The aim of this study was to identify clinical and echocardiographic factors influencing SC of isolated VSD in the first year of life among a group of patients presented at the Paediatric Clinic. Methods: Prospective study was performed in 60 consecutive patients with trivial, small or medium isolated VSD during the first year of life. Patients were divided into groups, according to gender and gestational age of the patient, type, number and the size of the defect and persistence of pulmonary hypertension. The size of defect was described in comparison to the diameter of the aortic annulus (VSD/Ao ratio). Results: At the time of diagnosis, the mean VSD/Ao ratio was 0.33 mm. Muscular VSD was more common (76.7 %) than perimembranous (23.3 %). SC of VSD occurred in 60 % of all patients, in case of muscular defect in 73.9 % and in case of perimembranous in 14.3 %. There was a negative correlation between defect size and SC rate. SC probability for a given defect size was described by the formula: probability = -1.82933X+1.20145. None defect with pulmonary hypertension closed. Conclusion: It was found that type and size of VSD and the persistence of pulmonary hypertension were significant predictors for SC, while gender and gestational age of the patient and the number of defects were not. This study can be useful in predicting the natural outcome of the VSD to make proper follow-up and management plans.